RECONCILING SCIENCE AND RELIGION BASED ON THE COMMON GOOD: REMEDY FOR ISLAMIC FUNDAMENTALISM AND PATH TOWARD DEMOCRACY - Aulia Shifa Hamida; Rahma Larasati; Sutan Akbar Kemal Syarief Putra Wibisana (UIN Raden Mas Said Surakarta, 2021)
Over the decades, there has been a growing understanding that emphasizes the separation between facts and values. Science is considered not to have the authority to answer questions related to morality. This article tries to offer a different argument emphasizing that science must have a role in answering various essential and urgent problems faced by many countries, namely, religious fundamentalism. This article offers a new synthesis of these relations based on the dialectical concept of two theories related to science and religion. Based on fiqh and the concept of maslahah, which have been the foundation for applying Islamic law, this article shows the positive relationship and the need for reconciliation between science and religion (Islam). Science turns out to offer an alternative solution, especially when there is the impossibility of separating religion and state. Reconciliation of science and religion (Islam) can contribute to the democratization process of Muslim countries without destroying Islamic religious values. The principle used is the concept of maslahah, whose focus orientation is for the common good.